Significance of transesophageal contrast echocardiography with the agitated saline test for diagnosing pulmonary arteriovenous malformations - Lim, Kyung Hee; Kim, Sung Mok; Park, Sung-Ji; Kim, Eun Kyoung; Chang, Sung-A; Lee, Sang-Chol; Park, Seung Woo; Choe, Yeon Hyeon (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study evaluated the diagnostic value of transesophageal contrast echocardiography (TECE) with the agitated saline test for diagnosing pulmonary arteriovenous malformations (PAVMs) in comparison with chest CT or pulmonary angiography. Background Although transthoracic contrast echocardiography (TTCE) is the recommended screening test for diagnosing PAVMs, it has low specificity and positive predictive value. TECE is expected to offer improved sensitivity and specificity compared with TTCE, but no studies have reported the diagnostic accuracy and clinical significance of TECE in detecting PAVMs. Methods and results In total, 1,809 patients underwent TECE with the agitated saline test to evaluate symptoms of a suspected right to left shunt. Patients with hereditary hemorrhagic telangiectasia (HHT) were excluded. A total of 387 patients showed transpulmonary bubble passage, indicating a PAVM. Among them, 182 patients had additional chest CT or pulmonary angiography. Those patients were divided into two groups according to the presence of a PAVM in the radiologic imaging. A total of 18 patients (9.8%) were confirmed for the PAVM group. Only 13 patients required embolization for their PAVMs. The TECE with saline test results were divided into four grades according to the number of bubbles: grade 1 (n = 91), grade 2 (n = 47), grade 3 (n = 35), and grade 4 (n = 9). None of the patients in the PAVM group had grade 1 shunts in their TECE results. The positive predictive values for the presence of a PAVM according to the TECE grade scale were 10.6% for grade 2, 22.8% for grade 3, and 55.6% for grade 4. Conclusion TECE with a grade scale is a useful method for initially diagnosing PAVMs in non-HHT patients with a suspected right to left shunt. The findings of this study also suggest that patients with a small grade (<10 bubbles) shunt in their TECE findings should be spared unnecessary radiation exposure from CT scans or pulmonary angiography.